Quantitative effects of sodium–glucose cotransporter-2 inhibitors dapagliflozin and empagliflozin on quality of life in heart failure patients - Wang, Dong-Dong; Zhang, Cun; Zhu, Ping; He, Su-Mei; Chen, Xiao (Frontiers in Pharmacology, 2022)
The present study is to investigate the quantitative effects of sodium-glucose cotransporter-2 (SGLT-2) inhibitors on quality of life in heart failure (HF) patients. 14,674 HF patients from two dapagliflozin studies and three empagliflozin studies are included for analysis via nonlinear mixed effect modeling (NONMEM), among which the change rate of Kansas City Cardiomyopathy Questionnaire (KCCQ) score is used as the evaluation index. There is no significant difference in pharmacodynamics influencing quality of life in HF patients between SGLT-2 inhibitors, 10 mg/day dapagliflozin and 10 mg/day empagliflozin. For clinical summary score (CSS), total symptom score (TSS), and overall summary score (OSS), the Emax of SGLT-2 inhibitors on quality of life in HF patients are 3.74%, 4.43%, and 4.84% respectively, and the ET50 are 2.23 weeks, 4.37 weeks, and 7.15 weeks, respectively. In addition, the duration time of achieving 25%, 50%, 75% and 80% Emax are 0.75 weeks, 2.23 weeks, 6.69 weeks, 8.92 weeks in CSS, 1.46 weeks, 4.37 weeks, 13.11 weeks, 17.48 weeks in TSS, 2.39 weeks, 7.15 weeks, 21.45 weeks, 28.6 weeks in OSS, respectively. Therefore, to reach the plateau period (80% of Emax) of SGLT-2 inhibitors on CSS, TSS, and OSS, 10 mg/day dapagliflozin (or 10 mg/day empagliflozin) need to be taken for 8.92 weeks, 17.48 weeks, and 28.6 weeks respectively. It is the first time to explore the quantitative effects of SGLT-2 inhibitors on quality of life in HF patients.